2, 4-D–Resistant Buckhorn Plantain (Plantago lanceolata) in Managed Turf. (1st February 2018) - Patton, Aaron J.; Weisenberger, Daniel V.; Schortgen, Geoff P.
Abstract: A population of buckhorn plantain with suspected resistance to 2, 4-D was identified in central Indiana following 30 yr of 2, 4-D–containing herbicide applications. Our objectives were to (1) confirm and quantify the level of herbicide resistance in the buckhorn plantain population using dose–response experiments and (2) find alternative herbicides that could be used to control this population. Greenhouse experiments were conducted to quantify the dose–response of resistant (R) and susceptible (S) biotypes of buckhorn plantain to both 2, 4-D and triclopyr, two synthetic auxin herbicides from different chemical families. The R biotype was ≥6.2 times less sensitive to 2, 4-D than the S biotype. The efficacy of triclopyr was similar on both the R and S biotypes of buckhorn plantain, suggesting the absence of cross-resistance to this herbicide. This is the first report of 2, 4-D resistance in buckhorn plantain and the first report of 2, 4-D resistance in turf. The resistance mechanism was limited to within a chemical family (phenoxycarboxylic acid) and did not occur across all WSSA Group 4 synthetic auxin herbicides, as the pyridinecarboxylic acid herbicides clopyralid and triclopyr and the arylpicolinate herbicide halauxifen-methyl provided control in our experiments.